Wetland characteristics influence disease risk for a threatened amphibian. Issue 4 (1st June 2014) - Heard, Geoffrey W.; Scroggie, Michael P.; Clemann, Nick; Ramsey, David S. L.
Abstract : Identifying determinants of the probability and intensity of infections is important for understanding the epidemiology of wildlife diseases, and for managing their impact on threatened species. Chytridiomycosis, caused by the fungal pathogen Batrachochytrium dendrobatidis, has decimated populations of some amphibians. However, recent studies have identified important environmental constraints on the disease, related to the pathogen's physiological tolerances. In this study, we identified several intrinsic and extrinsic determinants of the probability and intensity of chytrid infections for the threatened growling grass frog ( Litoria raniformis ) in southeastern Australia, and used mark–recapture to estimate the effect of chytrid infections on the probability of survival of these frogs. Water temperature and salinity had negative effects on both the probability and intensity of chytrid infections. We coupled models of the infection process with a model of the effect of chytrid infections on the probability of survival to assess variation in the impact of chytridiomycosis between wetlands with differing temperature and salinity profiles. Our results suggest that warm, saline wetlands may be refuges from chytridiomycosis for L. raniformis, and should be priorities for protection. Our results also suggest that management actions that increase water temperature (e.g., reducing canopy shading) and salinity (e.g., complementing inflows with groundwater) could be trialed to reduce the impacts of chytridiomycosis on this species. This and other recent studies highlight the value of research on environmental risk factors for chytridiomycosis.